Presentation EDUCA - UMCH journal N° 08 - Editorial, Comité (2016)
The EDUCA-UMCH MAGAZINE fulfills its institutional function by presenting the number 8, with topics of various kinds, the result of thinking and the research work of teachers at the University. With this, he disseminates works that show some brushstrokes of the teaching concern in the various fields of teaching and in the achievement of student learning, as well as his dedication to research and essays in the field of humanities, science Social and literature.